PENERAPAN DISTRIBUSI PELUANG UNTUK IDENTIFIKASI PERUBAHAN KLIMATOLOGIS CURAH HUJAN EKSTRIM - Visa, Juniarti (MATEMATIKA, 2005)
Climatological change analysis of rain fall in Maros and Ciamis had been done using rain fall data for 103 years. The rain fall process was focused in wet months (DJF) and dry months (JJA). The results show that in Maros and Ciamis area there had been a rain fall climatological change in every 30 years an average period. Using Statistical Distribution method, an extreme rain fall occurred in each period. The maximum rain fall in Maros was 1937 mm/month for wet months (DJF) and 316 mm/month, while in Ciamis was 1039 mm/month for wet month and 1199mm/month for dry month.